From 3D printing to 4D printing - Tan, Benjamin Zhi Wei (2017)
As 3D printing becomes increasingly popular as well as more affordable to the general public, we are looking for new ways to innovate through this manufacturing process. This paper explores the possibilities of 4D function through 3D printing. The project looks to identify possible methods to create a 3D printed model that will allow for compliant buckling of features within an object. This should allow the object to achieve bi-stability through these compliant mechanism features. Another key aspect to this approach is the use of shape memory materials that exhibit shape memory effect properties. These materials will react by methods of heating and cooling. Thus allowing programmable features in terms of controlling how different layers of features act within a model. This is valuable to the project as it allows for the control of the sequence of buckling. Throughout the project, different materials such as Polylactic acid, PLA as well as acrylic, Poly(methyl methacrylate) – PMMA, will be used to demonstrate these concepts. PLA was used for the printing of 3D modelled objects in the first cylindrical design as well as the hollow 3D model. PMMA was used for the constructing of a bi-stable, compliant mechanism array that demonstrates the features of how layers of the same pattern would be able to buckle or collapse in a sequential manner. The report also looks into why it is more practical to design such features to be printed through 3D printing instead of traditional methods like moulding and casting. The hollow 3D model that was designed had flaws in the print and showed that certain factors and considerations had to be noted in order to overcome the shortcomings of the 3D printer for such a design. The results at the end of the report show that with further improvements it is indeed possible to design and 3D model such an object that will be of a bi-stable, compliant nature.